2018
DOI: 10.1093/femsec/fiy166
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of plasmid-mediated AmpC beta-lactamase- and extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae among corvids (Corvus brachyrhynchos and Corvus corax) roosting in Canada

Abstract: This study evaluated the carriage of AmpC and extended-spectrum beta-lactamase (ESBL) genes and associated plasmids in faecal bacteria of Canadian corvids. Faecal samples from 449 birds in five roosting sites across Canada were analyzed using selective media, screening for AmpC and ESBL genes by PCR, and sequencing. Genomic relatedness was determined by PFGE and MLST. Plasmid mobility was studied by conjugation and transformation experiments, followed by plasmid typing. In total, 96 (21%, n = 449) cefotaxime-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We found a predominance of bla cmy-2 gene in the AmpC phenotype in the crow (16.8%) and water (18.36%) isolates. bla cmy-2 has been shown to be the most common plasmid borne beta lactamase in human, animal, and environmental bacterial isolates, and that includes large corvids in United States and Canada (Pitout et al, 2007; Mataseje et al, 2010; Folster et al, 2011; Martin et al, 2012; Jamborova et al, 2017, 2018). In a recent report 18.7% of Corvids from Canada were shown to carry the bla cmy-2 , which was substantially more than that reported from Corvids from European countries (4.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a predominance of bla cmy-2 gene in the AmpC phenotype in the crow (16.8%) and water (18.36%) isolates. bla cmy-2 has been shown to be the most common plasmid borne beta lactamase in human, animal, and environmental bacterial isolates, and that includes large corvids in United States and Canada (Pitout et al, 2007; Mataseje et al, 2010; Folster et al, 2011; Martin et al, 2012; Jamborova et al, 2017, 2018). In a recent report 18.7% of Corvids from Canada were shown to carry the bla cmy-2 , which was substantially more than that reported from Corvids from European countries (4.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, crows can acquire AR bacteria by foraging on a variety of wastes such as garbage dumps, hospital and animal wastes, and animal feed lots (Verbeek and Caffrey, 2002; Guenther et al, 2011). Several recent studies have reported crows and rooks shedding bacteria that were resistant to one or more antibiotics (Literak et al, 2007; Hasan et al, 2015; Jamborova et al, 2015, 2018). E. coli , which lives as a harmless commensal in the gut of all animal and birds, has proved to be not only an indicator of fecal coliform but also of antibiotic resistance present in the environment (van Den Bogaard et al, 2000; Dolejská et al, 2009; Guenther et al, 2011; Jamborova et al, 2015, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies were also based on fecal dejections collected in various places where birds live or transit, such as landfills, beaches, urban parks, nests, and other habitats, but associating fecal samples to the right bird species may be challenging. In some situations however, these approaches valuably allowed studying AMR in large cohorts of individuals of the same bird species in their natural environment, as for instance illustrated for black kites ( Milvus milvus ), corvids ( Corvus brachyrhynchos , Corvus corax ), gulls ( Larus glaucescens, Larus ridibundus ), pigeons ( Columba livia ) or storks ( Ciconia ciconia ) ( Bonnedahl et al, 2010 , 2014 ; Jamborova et al, 2018 ; Tarabai et al, 2019 ; Zendri et al, 2020 ). Here, we adopted a different strategy by systematically sampling all incoming wild birds at a French rescue center over a 6-month period.…”
Section: Introductionmentioning
confidence: 99%
“…Exploratory work, primarily in the form of cross-sectional surveys, has demonstrated that avian and mammalian wildlife may carry a variety of zoonotic agents (e.g., Salmonella, Campylobacter), some of which have been shown to be resistant to antimicrobials considered critical to human health [6][7][8]. In addition, bacterial clones of international importance (e.g., E. coli ST131), extended spectrum beta-lactamase-producers (ESBLs), and organisms resistant to last-resort antimicrobials (e.g., colistin, vancomycin, carbepenems) mediated by mobile resistance genes have all been isolated from and documented [9][10][11][12][13][14][15][16]. Much of the work examining the epidemiology of AMR in wildlife has been focused on wild birds [4,17,18].…”
Section: Introductionmentioning
confidence: 99%